Studi Geologi Daerah Makale Dan Sekitarnya, Kabupaten Tana Toraja, Provinsi Sulawesi Selatan - Putri Wulan Rahmawati; Fitryane Lihawa; Noviar Akase (-, 2026)
The Makale area, Tana Toraja, South Sulawesi (119°19′05″–120°09′16″ E; 02°36′03″–03°24′13″ S) features a complex geological setting with limited detailed data. This study maps its geology through 54 observation stations, thin-section petrography, geomorphological classification, and Landsat 8 band 5-6-7 lineament interpretation. Stratigraphically, the area comprises four units from oldest to youngest: Early–Middle Miocene Makale Formation limestones, classified as Foraminiferal Rudstone (±28%, grain-supported, 1% porosity) and Foraminiferal Packstone (±29%, mud-supported, 2% porosity) per Embry and Klovan (1971); the Middle Miocene–Pliocene Sekala Formation sandstone (±20%); and the youngest alluvial deposits (±24%). Geomorphologically, the terrain is divided into karst hills with tower karst morphology (±57%), denudational hills (±20%), and fluvial valleys (±24%). Lineament analysis reveals a dominant north–south structural trend, validated by field lithological contacts.